Star Wars and the State of Our Souls. Special Issue. The Whole Earth Papers, No. 20 - Mische, Patricia M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
These two essays are intended to make U.S. citizens think about what they are doing, to put contemplation before action when considering the "Star Wars" proposals, i.e., proposals for research, development, and testing of space weapons. It is emphasized that the "Star Wars" proposals offer no real breakthroughs in strengthening national security or world security. The first essay, "Star Wars and the State of Our Souls," discusses the weaponization of space, space dedicated to peace, preparing for star wars, types of space weapons, how weapons determine policy, arguments of proponents and opponents of "Star Wars," the real objectives of "Star Wars," the need for people to really think about what "Star Wars" would mean, and the benefits of a ban on space weapons. The second essay,"Space Weapons: A Workable Defense Or a Faustian Bargain?" describes and assesses anti-satellite weapons and "Star Wars" technology and proposes a ban on space weapons. The publication concludes with a "Proposal for a Deep Freeze" by Robert M. Bowman. (RM)
Availability: Global Education Associates, 552 Park Ave., East Orange, NJ 07017 ($2.50; bulk rates available).
Microfiche.
Keywords: Disarmament; Foreign Policy; National Security; Nuclear Warfare; Nuclear Weapons; Peace; Outer Space -- Space Weapons -- Star Wars; Nuclear Deterrence -- Nuclear Freeze; Opinion Papers